Modernising Public Administration: Reimagining Public Administration for the Digital Age - Baummar, Mael (Közigazgatási és Infokommunikációs Jogi PhD Tanulmányok, 2024)
This article examines the imperative of digital transformation for modernising public administration in response to contemporary challenges and technological advancements. The discussion centres on the evolving conceptualisation of public administration and cites legislative initiatives highlighting the importance of citizen involvement as a crucial element of governance. This article uses academic perspectives to examine digital transformation as a strategic approach, focussing on process optimisation, data-driven decision-making, and transparency. The article underlies the development of citizens' expectations in the digital age, which requires a fundamental rethink in the provision of services by public administration. Besides, the article addresses the challenges and opportunities in modernisation, focusing on legacy systems and infrastructure limitations.